Effect of Garcinia Cambogia Extract on Body Weight, and Evaluation of Histological, Physiological, and Biochemical Changes in the Prostate Gland of Adult Albino Wistar Rats: An Anatomical Perspective - Naeem Shahzad, Riffat Naeem, Durre Shehwar, Muhammad Faheem Siddiqui, Qanbar Abbas Naqvi, Muhammad Yasoob, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: As obesity's prevalence has increased recently and is related to a number of disorders such as diabetes, hypertension, cardiovascular, hyperlipidemia, fatty liver, osteoarthritis, and mental health issues, it has been deemed a public health issue. Hydroxycitric acid, a phytochemical found in Garcinia cambogia, plays a significant role in weight loss by inhibiting fat synthesis and weight gain. Garcinia cambogia also contains an antioxidant, Garcinia hydroxybiflavanonol (GB1) which has the potential to improve testosterone levels. Aim: To measure and compare the body weight of adult albino Wistar rats, to evaluate the histological changes on epithelium of prostatic acini and to compare the testosterone levels among the groups after Garcinia cambogia extract administration. Methods: A randomized controlled experimental study was performed at Postgraduate Medical Institute (PGMI), Lahore on 24 male albino Wistar rats, in which 3 groupings were formed with eight rats each, aged of 6 to 8 weeks where group A was considered as control group, B (given a sub-toxic dose of about 778 mg/kg weight of Garcinia cambogia) and C (given a toxic dose which was 1244 mg/kg body weight of Garcinia cambogia) for 28 consecutive days through gavage method. The data obtained from the Group A was compared with data gained from the Group B and C. Results were analysed using SPSS version 25.0 The cutoff for statistical significance was p ≤ 0.05. Results: Significant weight loss in Garcinia cambogia treated groups in comparison with Control group.Animals in Garcinia cambogia treated groups had remarkably lower mean body weights than those in group A.Cellular vacuolization and markedly elevated testosterone levels were documented in the treated groups. Conclusion: Garcinia cambogia was found to raise testosterone levels and have a positive effect on obesity in this study. Keywords: Garcinia cambogia, hydroxycitric acid, garcinia hydroxybiflavanonol, obesity, hypertension